ANALISA KEGAGALAN MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALISYS (FMEA) PADA UNIT OFF-HIGHWAY TRUCK 777D - Candra Dwi Putra; Akhmad Syarief; Hajar Isworo (Scientific Journal of Mechanical Engineering Kinematika, 2018)
Heavy equipment is a tool used to assist humans in performing construction and manufacturing projects to support good governance in the development of infrastructure as well as in the mining process. In use, heavy equipment is not a tool that has never experienced a failure in the system or group component, also in product design even on the work process during its life cycle which will lead to some disadvantages like low levels of production, not achieving the timetable or targets that have been set and also losses from repairing costs. Therefore, it is necessary to analyze the systems or any component group that experienced failure the most in the heavy equipment and also need to provide a "value" on the failure. With this, it’s expected to help prevent a decrease in productivity by taking action a precaution against the systems that have high failure value. Value of the failure can be calculated based on unscheduled breakdown data that processed using Failure Mode and Effect Analysis (FMEA). This research was conducted using primary data obtained from the data breakdown and by collecting supporting data relating to the object of the report. With this research, it can be obtained the system or component group that has the largest failure value on the heavy equipment.